Midterm Results of Radiofrequency Ablation for Incompetent Small Saphenous Vein in Terms of Recanalization and Sural Neuritis. Issue 4 (20th February 2014) - Park, Jae Young; Galimzahn, Azimbaev; Park, Hyung Sub; Yoo, Young Sun; Lee, Taeseung
<x xml:space="preserve">Abstract</x> Background Safety and effectiveness of radiofrequency ablation for incompetent small saphenous vein is not established. Objective To report midterm clinical and ultrasonograhic results of radiofrequency ablation (RFA) for small saphenous vein (SSV) in terms of recanalization and sural neuritis. Methods and materials We examined 39 patients (46 limbs) who had been examined using a duplex scan more than 1 year after RFA of SSV. Postoperative clinical results, risk factors for SSV recanalization, and sural neuritis were analyzed. Results CEAP score and CIVIQ2 score improved significantly in all patients (CEAP: 2.45 to 1.43 (p = .03); CIVIQ2: 25.34 to 13.21 (p = .01). SSV obliteration rate was 93.4% at 1 year and 89.1% at 2 years. Preoperative peak reflux velocity in the recanalization group (54.9 cm/s) was significantly higher (p < .01) than in the obliteration group (29.8 cm/s). Sural neuritis were detected in 12 limbs (26.1%), and median symptom duration was 3 months. The total length of RFA ablation was not different between the groups with and without postablation sural neuritis. Conclusion RFA is an effective and safe treatment modality for incompetent SSV. Peak reflux velocity can be a risk factor for recanalization. Length of RFA segment in SSV does not affect recanalization and postablation sural neuritis.